Основні моделі побудови системи місцевого самоврядування в містах України - Бальций Юрій Юрійович; Бальций Юрий Юрьевич; Bal'cij Jurij (My University, 2013)
Article is devoted to the study of the basic models of the system of local self-government in the cities of Ukraine. It was determined that the basic model of the system of local government in the cities of Ukraine are the following: «the council — Mayor», «City Council — Dis-trict Council», «city council — the ad-ministration of the city council in the area», «the council — the state admin-istration».
Бальций Ю. Основні моделі побудови системи місцевого самоврядування в містах України / Ю. Бальций // юридичний вісник. - 2013. - № 4. - С. 35-38.
Keywords: місцеве самоврядування; моделі системи місцевого самоврядування; реалізація народовладдя; організація місцевого самоврядування; местное самоуправление; модели системы местного самоуправления; реализация народовластия; организация местного самоуправления; local government; model of local self-government; realization of democracy; organization of local self-government